Does the Fix- Up Strategy Affect Indonesian EFL Learners’ Reading Comprehension? - Rusmiati Rusmiati; Irnasari Irnasari; Saiful Akmal (English Department FBS UNP, 2022)
Gaining comprehension when reading has become a challenge for students in EFL context. The present study was undertaken to deal with the hardship that EFL learners confront in their reading class. A strategy called fix up was considered effective in coping with the issue. This research employed a quantitative approach with an experimental design involving 40 students from a senior high school in Takengon, Aceh Tengah, Indonesia. They were equally divided into experimental and control groups, each consisting of 20 students. The instrument utilized here was a test comprising 25 multiple-choice questions, which has passed through validity and reliability test. The scores were analyzed by utilizing a t-test. The results showed that the learners in experimental group performed a much more significant increase compared to those in the control group. In addition, t-score was found greater than the t-table (6, 66 > 2,024) at a significance level of 0, 05 with df (38) suggesting that H0 was rejected and Ha was accepted. It can be concluded that the fix-up strategy affects the students’ reading comprehension, and it is recommended that other English instructors apply this strategy to create more active learners and to provide a better learning circumstance.